1-methylnicotinamide modulates IL-10 secretion and voriconazole metabolism - Deng, Xiaoyan; Li, Yuanqing; Jiang, Lin; Xie, Xuqiu; Wang, Xiaokang (Frontiers in Immunology, 2025)
BackgroundInflammatory diseases impair the hepatic metabolism of voriconazole (VRC). 1-Methylnicotinamide (1-MNA), a common final metabolite of nicotinamide in the liver, has demonstrated anti-inflammatory effects in recent studies. This study investigated the impact of 1-MNA on VRC metabolism in the liver.MethodMice with a systemic inflammatory response induced by lipopolysaccharide (LPS) were intragastrically administered 1-MNA, and their VRC metabolic capacity was evaluated. Kupffer cells and primary hepatocytes were isolated, and flow cytometry along with molecular knockdown experiments were performed to explore the molecular mechanisms underlying improved drug metabolism. IL-10 knockout (IL-10–/–) mice were used to validate the role of IL-10 in enhancing hepatocyte VRC metabolism under inflammatory conditions.Results1-MNA promoted M2 polarization of liver Kupffer cells, stimulated IL-10 secretion, upregulated CYP2C38 expression in primary hepatocytes, and enhanced VRC metabolism. The mechanism by which IL-10 upregulated CYP2C38 appears to involve the inhibition of the nuclear transcription factor NF-κB (p65) in hepatocytes.Conclusions1-MNA regulated Kupffer cell polarization in an LPS-induced inflammatory environment, reduced the inflammatory inhibition of CYP2C38 expression in hepatocytes, and promoted VRC metabolism.